The postbiotic sodium butyrate synergizes the antiproliferative effects of dexamethasone against the AGS gastric adenocarcinoma cells - Eladwy, Radwa A; Alsherbiny, Muhammad A.; Chang, Dennis; Fares, Mohamed; Li, Chun-Guang; Bhuyan, Deep Jyoti (Frontiers in Nutrition, 2024)
A growing body of literature underlines the fundamental role of gut microbiota in the occurrence, treatment, and prognosis of cancer. In particular, the activity of gut microbial metabolites (also known as postbiotics) against different cancer types has been recently reported in several studies. However, their in-depth molecular mechanisms of action and potential interactions with standard chemotherapeutic drugs remain to be fully understood. This research investigates the antiproliferative activities of postbiotics-short-chain fatty acid (SCFA) salts, specifically magnesium acetate (MgA), sodium propionate (NaP), and sodium butyrate (NaB), against the AGS gastric adenocarcinoma cells. Furthermore, the potential synergistic interactions between the most active SCFA salt-NaB and the standard drug dexamethasone (Dex) were explored using the combination index model. The molecular mechanisms of the synergy were investigated using reactive oxygen species (ROS), flow cytometry and biochemometric and liquid chromatography-mass spectrometry (LC-MS)-driven proteomics analyses. NaB exhibited the most significant inhibitory effect (p < 0.05) among the tested SCFA salts against the AGS gastric cancer cells. Additionally, Dex and NaB exhibited strong synergy at a 2:8 ratio (40 μg/mL Dex + 2400 μg/mL NaB) with significantly greater inhibitory activity (p < 0.05) compared to the mono treatments against the AGS gastric cancer cells. MgA and NaP reduced ROS production, while NaB exhibited pro-oxidative properties. Dex displayed antioxidative effects, and the combination of Dex and NaB (2:8) demonstrated a unique pattern, potentially counteracting the prooxidative effects of NaB, highlighting an interaction. Dex and NaB individually and in combination (Dex:NaB 40:2400 μg/mL) induced significant changes in cell populations, suggesting a shift towards apoptosis (p < 0.0001). Analysis of dysregulated proteins in the AGS cells treated with the synergistic combination revealed notable downregulation of the oncogene TNS4, suggesting a potential mechanism for the observed antiproliferative effects. These findings propose the potential implementation of NaB as an adjuvant therapy with Dex. Further investigations into additional combination therapies, in-depth studies of the molecular mechanisms, and in vivo research will provide deeper insights into the use of these postbiotics in cancer, particularly in gastric malignancies.